Rekonstruksi Pengaturan Kampanye Legislatif Dalam Undang-Undang Nomor 7 Tahun 2017 - M. Nashrulloh Akbar (SAPIENTIA ET VIRTUS, 2018)
One of the significant piece of election is the campaign conducted by the election participants. To achieve an integrated election, the campaign must guarantee the free and fair principles and legal certainty. This research looks to how the regulation works as a reference to campaign implementation. The emergence of election law 7 Tahun 2017 is expected to cover the weakness of previous legilslation 8 Tahun 2012. Evidently, the regulations can not guarantee the legal certainty on campaign implementation that caused many problems in its aplication. Therefore the reconstruction of regulation must be carried out in order to create free and fair competition for elections with integrity.